Etnomatematika: Eksplorasi Konsep Geometri di Sekolah Dasar dalam Kearifan Lokal kain Songket dan Pakaian Melayu - Ain, Siti Quratul; Lingga, Leny Julia; Sakila, Nesa; Yoanda , Windi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Mathematics learning in elementary schools is often considered abstract and detached from the context of everyday life. Findings in the field, the low ability of students to understand concepts and the lack of knowledge related to culture are the main problems that need to be solved. One alternative approach used to bridge this gap is ethnomathematics, namely by linking mathematical concepts with local culture. This study aims to explore the integration of geometric concepts in the local wisdom of songket cloth and Malay clothing in mathematics learning in elementary schools. The research method used is qualitative with an ethnographic approach. Data were collected through participatory observation, interviews and visual documentation of the motifs and structures of traditional clothing such as teluk belanga, cekak musang and kekek. The results showed that motifs such as pucuk rebung, siku keluang, and bunga cengkih reflect geometric concepts such as symmetry, reflection, rotation, and translation. In addition, elements of Malay clothing reflect the forms of flat and spatial shapes, which can be used to teach the concepts of area and volume. This integration not only enriches the learning material, but also increases students' interest and motivation to learn because the material is presented through a cultural approach that is close to their lives. The conclusion of this study is that the ethnomathematics approach based on local culture has great potential in improving students' conceptual understanding of geometry while preserving cultural heritage.